Synthesis and Catalytic Properties of New Metalloporphyrin‐Based Porous Organic Framework Materials with Single and Accessible Sites. Issue 14 (15th June 2016) - Meng, Shuang; Zou, Xiaoqin; Liu, Chuanfang; Ma, Heping; Zhao, Nian; Ren, Hao; Jia, Mingjun; Liu, Jia; Zhu, Guangshan
Abstract: It is a big challenge to homogenize heterogeneous catalysts with molecular catalytic performance. With this target in mind, herein, we describe a facile strategy for direct incorporation of single catalytic sites in 3D open porous aromatic frameworks (PAFs). The synthesis of the PAF (denoted as PAF‐76) as well as its derivatives (PAF‐76‐M, M=Fe, Mn, Zn) was achieved by the use of tetrakis(4‐bromophenyl)methane as tetrahedral nodes and tetrakis(4‐bromophenyl)porphyrin as planar nodes. The connection of monomers into an extended network of PAF‐76 was monitored by 13 C NMR and FTIR spectroscopies. The prepared PAF‐76s showed 3D porous structures with surface areas of 450–700 m 2  g −1, pore volumes of 0.3–0.4 cm 3  g −1, and pore sizes around 1.2 nm. The direct incorporation of metalloporphyrin components into the PAF‐76‐M frameworks has allowed the uniform distribution of metal ionic sites throughout the PAF‐76‐M particles. The combined merits of isolated metal sites and suitable pore size make PAF‐76 a good candidate for heterogeneous catalysis. The catalytic performances of the porphyrin/metalloporphyrin‐based active sites in the PAF‐76s were evaluated by aerobic oxidation reactions of styrene, which are usually carried out with homogeneous systems. Metal‐functionalized PAF‐76s (PAF‐76‐M) exhibit enhanced turnover frequencies for styrene conversion (16.9–50.9 mol mol(M) −1  h −1 ) compared with molecular catalysts (0–35.0 mol mol(M) −1  h −1 ), and improved selectivity toward phenylacetaldehyde (85.7–99 %) in contrast to their corresponding monomers (0–75.5 %). The robustness of PAF‐76 in terms of high thermal stability, good recyclability, and excellent solvent resistance showed that these PAF‐76 materials hold great promise for developing heterogeneous catalysts. Abstract : Homo‐heterogeneous POF catalysts : Porous organic framework (POF) materials (PAF‐76) with metalloporphyrin components in the frameworks have been prepared by a direct synthesis approach. The as‐prepared PAF‐76 materials possess three‐dimensional conjugated networks, permanent porosity, as well as single and accessible metalloporphyrin active sites. The catalytic properties of PAF‐76 catalysts were evaluated for the aerobic oxidation of styrenes, and the catalytic results reveal that PAF‐76s exhibit superior performance in terms of high turnover frequency and good product selectivity. The above merits along with the robustness hold great promise for PAF‐76 materials in heterogeneous catalysis.